Superficial Acid-Base Properties of Polymer Fibres; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Lysak I. A. Ilya Aleksandrovich; Skvortsova L. Lidia; Lysak G. Galina; Malinovskaya T. Tatiana; Sherstoboeva M. Maria (Synthesis and physicochemical characteristics of materials, 2016)
Title screen